Stigma and Discrimination During COVID-19 Pandemic - Bhanot, Divya; Singh, Tushar; Verma, Sunil K.; Sharad, Shivantika (Frontiers in Public Health, 2021)
The COVID-19 pandemic has been instrumental in creating a dramatic shift from people’s need to live in mutual association towards a desire to stigmatize distinctive others (Earnshaw, 2020). Pandemic seems to be causing othering. Stated simply, stigmatization is a social process set to exclude those who are perceived to be a potential source of disease and may pose threat to the effective social living in the society (Barreto, 2015; Phelan et al., 2008). Based on the secondary evidence collected from news published online or in print, the present paper delves into stigma associated with the COVID-19 pandemic amongst different social groups in the Indian society and the mounting cases of prejudice based on race, class, and religion. It also presents insights into the varied manifestations and the deleterious consequences of COVID-19 inspired othering brought to its potential targets in India.